A new species of Discospermum (Coffeeae, Rubiaceae) from Luzon, Philippines including its conservation status - Arriola, Axel Havana; Alejandro, Grecebio Jonathan (Phytotaxa, 2015)
Discospermum philippinensis, a new endemic species from the Philippines, is here described and illustrated. The species is similar to D. whitfordii because of a persistent calyx and a prominent disk below the fruit apex, from which it can be distinguished by leaf blades 5.5–15.5 × 3.5–6.5 cm, acute to attenuate leaf apex (vs. 4.5–10.0 × 2.0–4.5, caudate in D. whitfordii), fruits faintly ribbed, smaller with thin mesocarp (vs. non-ribbed, with a thick mesocarp), and 4–6 seeds per locule (vs. 5–12).